Argumentação e discurso político : uma proposta para o ensino de língua portuguesa nas séries finais do ensino fundamental - Silveira, Josefa Almeida da (2016)
This work, entitled Argumentation and political discourse: a proposal for the Portuguese Language teaching in the final grades of Elementary School, presents a suggestion for the application of the mother tongue from oral / written argumentative. It is based on concepts of orality, text production, argumentation and political discourse in the view of many scholars, as Aristóteles (2013), Bakhtin (1997, 1981), Fiorin (2015), Fulaneti and Bueno (2013), Grácio (2010, 2013), Koch (2011, 2012, 2015), Marcuschi (2008), Osakabe (2002), Perelman e Tyteca (2005), and others; the norms of the National Curriculum Parameters (1997, 1998) and the National Curriculum Guidelines for Basic Education (2013). It aims to propose the development of the capacity of critical thinking, reflective reading, organization of ideas, enabling elementary school students (9th grade) of a state college, located in Campo do Brito / SE, for the competence of argumentative communication, with oral and written textual activities, from language understanding as a form of interaction in order to optimize the capacity of analysis and the construction of arguments in political discourse. The speeches will be observed, compared and analyzed on viewpoint of argumentation and confronted with problems experienced by the general population, using records, photos and interviews, collected by students in the community. And, in the final stage, after discussion and reflection on the political role and about which main questions need further attention of public authority, we propose a written textual production of a letter to the people, consistent, covering the problems found and the suggestion of proposals, guided in arguments. The proposal is replace a purely legal education to a more reflective teaching with opportunities for reading, debates, with oral and written production, significantly, considering that reading, interpretation, writing and argumentation are essential in language learning, understanding teaching as an interactive activity of expression for critical student, autonomous, thinks about what he will write, who will write for, and the object of production. It proposes a teaching practice with emphasis on argumentative strategies in order to form a student reader / producer of texts, allowing the exercise of citizenship.